ANALISA REAKSI PASAR TERHADAP INVASI RUSIA KE UKRAINA PADA PERUSAHAAN INDUSTRI ENERGI YANG TERDAFTAR DI BEI - Nasution, Yuslinda; Ristiana (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
ABSTRACTSince the Russian invasion of Ukraine caused a shift in stock prices and sales levels, this is the reason researchers conduct research related to differences in stock prices. Observations were made 30 days before and 30 days after the announcement of the Russian invasion of Ukraine. Sampling used a purposive sampling technique, the sample in this study consisted of 73 energy companies listed on the Indonesia Stock Exchange. The Wilxocon sign test was used in this study. From the results of the study, it was found that the stock price and sales volume did not change before and after the Russian invasion of Ukraine. There is no difference in stock prices and sales volume as evidenced by the fact that usually abnormal returns and trading volume did not increase or decrease significantly either from the beginning or after the attack from Russia on UkraineKeywords: Announcement of the Russian Invasion of Ukraine, Corporate Actions, Average Abnormal Return, Trading Volume Activity.